Residual Stress, Thermomechanics & Infrared Imaging, Hybrid Techniques and Inverse Problems, Volume 9 Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics - Bossuyt, Sven; Schajer, Gary; Carpinteri, Alberto (Conference Proceedings of the Society for Experimental Mechanics Series, 2016)
Residual Stress, Thermomechanics& Infrared Imaging, Hybrid Techniques and Inverse Problems, Volume 9 of the Proceedings of the 2015SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the ninth volume of nine from the Conference, brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on a wide range ofareas, including: Inverse Methods Inverse Methods in Plasticity Varying Length Scales Harsh Environments Opto-Acoustical Methods Hybrid Experimental Residual Stress Modelling and Advances in Measurements Thermomechanics General Material Response Infrared Imaging  .